Bantal Tilu Jamparing di KuruSetra: Bisma Gugur menurut Tradisi Mahabharata - Manu J. Widyaseputra (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2007)
This paper describes the narrative on the fall of Bisma, the first marshal of Kaurava, in the battle-field, KurukSetra, according to the Mahabharata of the Sundanese version. I present the epic-myth-ritual approach as Alf Hiltebeitel has conducted in his research on the Mahabharata in the Sanskrit and Tamil versions. My discussion begins with an introduction to the identity of Bisma in the Sundanese Mahabharata, followed by his heroic account in the Kuruksetra and his fall in the hand of srikandi and Arjuna. By applying the myth-ritual approach we can find that Bisma was Dyaus, 'the sky' in the past, so it is not surprising that when he fell in the battle-field, his body did not touch the earth, as it was sustained by the arrows of Srikandi and Arjuna. He lay down on the saratalpa, 'the bed of arrows', except his head. Arjuna helped him by shooting his three arrows to sustain his head. The three arrows means the Vedic fire which is used in the marriage. Bisma is celibate who needed the help of Arjuna to perfect his life.